Triggers and Determinants of Severe Household Indebtedness in Germany - Matthias Keese (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Overindebted private households have created economic and political concern. Using measures of relative (over-) indebtedness which relate household income and debt services to different concepts of subsistence levels, this paper investigates whether severe household indebtedness is driven by trigger events such as unemployment, childbirth, divorce, or the death of the partner. Exploiting the panel structure of the German Socio-Economic Panel (SOEP), the results suggest that children are likely to cause severe household indebtedness. Unemployment also worsens the relative debt situation mainly due to the associated income drop. Strokes of fate have no direct effect but if they come along with changes in household composition, the associated income shock increases the financial fragility of the household. Furthermore, a main determinant of relative overindebtedness is a home loan which raises doubts about whether families are indeed able to manage their housing finance.
Keywords: D12; D14; D91; 330; household finance; debt; overindebtedness; SOEP